IITA DG Sanginga inaugurates renovated facilities of virology and germplasm health units - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
DG Sanginga cuts the tape commissioning IITA Virology lab on 14 February 2019 at IITA Ibadan.